Are experimental protocols an authentic simile of human diabetes? - Moreno-Cortés, María Luisa (Universidad Autónoma de Tamaulipas, 2020)
For the study of diabetes, several methodological strategies use animal models. Such methodologies involve surgical techniques, diet modifications, some genetic manipulations and specific toxic drugs. The experimental production of diabetes in animal models use the administration of alloxan or streptozotocin and these drugs produce irreversible damage to pancreatic -cells. However, its use is associated to a ketosis high mortality rate due to the acute damage of pancreatic cells. The aim of this review consisted in the analysis of the pharmacological diabetes production protocols as well as other available strategies, in order to elucidate which is potentially the ideal protocol that emulates human diabetes. Diabetes is a progressive and chronic process, in which most of the clinical alterations are a long-term consequence of micro and macrovascular alterations. Therefore, it is convenient to establish a difference between the effects of acute hyperglycemia, with those effects observable when hyperglycemia is present over the long-term in order to reach enough analogies between the animal experimental model with the human diabetes syndrome, through the use of laboratory and clinical indicators commonly employed for the diagnoses and management of human diabetes.